Peran Supervisi Akademik dalam Meningkatkan Motivasi Belajar Siswa di SMP IT YASPIDA Sukabumi - Muhamad Wisnu; Siti Qomariyah; Neng Desti Ramadhani; Lusi Lusi (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to examine the role of academic supervision in improving student learning motivation at SMP IT YASPIDA SUKABUMI. Academic supervision is a systematic coaching effort for teachers to improve the quality of classroom learning. Student learning motivation is a crucial indicator of the success of the learning process, therefore, appropriate strategies are needed to improve it. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research was conducted with the goal of understanding how academic supervision influences teachers' pedagogical competence and, in turn, affects student motivation. The results show that structured and continuous academic supervision can significantly improve teachers' pedagogical competence, which in turn has a positive impact on student learning motivation. Collaborative supervision, providing constructive feedback, and focusing on improving the learning process have proven effective in creating a conducive and motivating learning environment. Teachers who receive regular supervision become more reflective and are better able to adapt their teaching strategies to meet students' needs. Consequently, this results in higher student engagement and a more enthusiastic learning atmosphere. Thus, academic supervision plays a strategic role in encouraging student learning enthusiasm by improving the quality of learning and ensuring that students are motivated to achieve better academic outcomes. This study highlights the importance of continuous academic supervision in fostering a positive learning environment and motivating students.